(untitled) (Economics and region, 2023)
The article analyzes the concept of "logistics potential" and its key elements and components. They point to the importance of logistics potential as a basis for implementing a logistics strategy in the region. The article analyzes that the logistics potential of the region is an important aspect for its economic development and competitiveness. The article examines the role and significance of logistics potential in the context of creating effective logistics systems based on innovative approaches and management of material and related flows. The article also examines the meaning of the concept of "logistics potential" and its essential characteristics. A systematization of interpretations of the concept of "logistics potential" by domestic and foreign economists has been carried out. It has been studied that the study of logistics potential allows to understand how to optimize the supply chain, reduce costs, improve the speed and reliability of the supply of goods and services, thereby contributing to the improvement of the efficiency of business processes and the competitiveness of enterprises. The key elements of the logistics potential are outlined, such as infrastructure, transport networks, warehouse facilities and a skilled workforce. They indicate the importance of the quality and availability of these components for optimizing logistics processes and ensuring the competitiveness of the region. The article emphasizes that the development of the logistics potential of the region contributes to the attraction of investments, business growth and the creation of new jobs. It also facilitates access to markets and reduces costs, which contributes to the overall improvement of the economic situation of the region. During the analysis of the logistics potential of the Lviv region, several key factors determining its efficiency and competitiveness were identified. First of all, the region benefits from its own geographical location, as international transport corridors pass through it, providing easy access to other countries’ markets. In general, the development of the logistics potential of the region is important for improving its economic position, competitiveness and ensuring sustainable development. Investments in infrastructure, workforce qualifications and innovative solutions are key factors for building the logistics potential of the region.